Strategic Approaches to Community Safety Initiative (SACSI) Research Partnership in Detroit, Michigan, 1999-2003 - Bynum, Timothy S. ([Verlag nicht ermittelbar], 2007)
The Strategic Approaches to Community Safety Initiative (SACSI), in Detroit, Michigan, involved a team of federal, state, and local agencies that worked together to systematically address gun violence in that city. The purpose of the SACSI project was to examine the dynamics of gun violence and the manner in which such cases are processed within the criminal justice system, and to evaluate two SACSI gun violence interventions in Detroit's Eighth Precinct. The first intervention, "Operation 8-Ball," was a warrant sweep aimed at gun-involved offenders with outstanding warrants, who were residing in the Eighth Precinct. Part 1, SACSI Monthly Gun Robberies Data, contains the monthly totals for stranger gun robberies in three Detroit precincts, collected to measure the impact of the "Operation 8-Ball" intensive warrant enforcement program conducted in late September 2001. Part 1, contains six variables. The second strategy for addressing gun violence adopted by the working group was a gun-involved parolee supervision component entitled the Detroit SACSI Parolee Initiative. Part 2, SACSI Monthly Contact for Parolees Data, contains the monthly totals for a variety of parole contacts, collected to measure the intensity of a supervision program implemented for gun offenders, which commenced in July 2002. Part 2 also contains levels of parole violations in an intensive parole group in the Eighth Precinct of Detroit. Part 2, contains 16 variables.